Hyaluronic acid predicts poor prognosis in breast cancer patients: A protocol for systematic review and meta analysis. Issue 22 (29th May 2020) - Wu, Weiping; Chen, Lifen; Wang, Yanzhong; Jin, Jing; Xie, Xinyou; Zhang, Jun
Abstract: Background: Hyaluronic acid (HA) may be a novel prognostic biomarker of breast cancer. However, the available evidence is controversial. Therefore, we performed a meta-analysis to determine the prognostic role of HA in breast cancer. Methods: The data were extracted from seven articles by searching the databases of PubMed, EMBASE, Web of Science, the Chinese National Knowledge Infrastructure and Wanfang data for the prognostic role of HA in breast cancer. In reference to survival outcomes, the pooled hazard ratios (HRs) of HA were calculated given a 95% confidence interval (CI). Results: A total of seven articles were included in our study involving 2664 cases. The result of meta-analysis showed that a high HA level predicts poor overall survival (OS) (HR = 1.86, 95% CI: 1.28–2.71, P  = .001) and shortened disease-free or recurrence-free survival or progression free survival (DFS/RFS/PFS) (HR = 1.63, 95% CI: 1.14–2.33, P  = .007) in breast cancer patients. Moreover, a high HA level in stroma (HR = 1.63, 95% CI: 1.06–2.51, P  = .025) and plasma (HR = 3.26, 95% CI: 2.25–4.73, P  < .001) significantly predicted poor OS. Besides, a tendency shows that HA was significantly correlated with lymph node metastasis (HR = 1.55, 95% CI: 0.96–2.49, P  = .070) and tumor grade (HR = 2.10, 95% CI: 0.89–4.96, P  = .089) on the clinical characteristics of patients. Conclusion: These results suggested that HA has a potential to be prognostic biomarker in breast cancer patients, especially location in stroma and plasma.